PENERAPAN STRATEGI PELAKSANAAN UNTUK MENINGKATKAN INTERAKSI PADA PASIEN SKIZOFRENIA DENGAN ISOLASI SOSIAL DI RSUD BANYUMAS - Fara Aprilia Rizqita Fara; Ririn Isma Sundari; Prasanti Adriani (JURNAL PENGABDIAN MANDIRI, 2022)
Mental health problems are currently still unresolved. One of the psychiatric disorders is schizophrenia. The causes of schizophrenia are genetic, psychosocial and spiritual. Symptoms of schizophrenia are divided into 2, one of which is negative symptoms, namely social isolation. Feelings of worthlessness make it difficult to interact with other people. In this case the nurse is tasked with re-increasing the patient's trust and teaching the patient to interact. research method using descriptive case studies. In carrying out nursing care to patients, patients are found to be able to interact again with other people.